Response Analysis of Training Participants of The Project Learning Integrated Ethno-Stem for The Study of Herbal Tea as A Covid-19 Immunity - Sudarmin, Sudarmin; Priatmoko, Sigit; Mahatmanti, F. ‪Widhi; Listiadji, Prasetyo; Pujiastuti, Rr. Sri Endang; Sasmita, M. (Universitas Negeri Semarang, 2024)
This time Indonesia is being hit by the Covid-19 pandemic, so it is important to introduce local plants as immunity to teachers and students. The purpose of this training is to provide knowledge and skills to recognize the Ethno-STEM integrated project learning model (PJBL) on the topic of local plant herbal teas and tropical forests as immunity. This training is important, because the results of interviews with several teachers and master students of chemistry education show that they have never received this training. This training activity was carried out at the UNNES Postgraduate online, as well as the practice of making tea and learning videos at the UNNES Chemistry Laboratory. The method of activity is through lectures, discussions, and herbal tea making practices, as well as evaluation. The target audience is teachers, 22 students of master's degree in education. The results of the training activity concluded that participants had acquired the knowledge and skills to design an integrated Ethno-STEM learning model for herbal teas and tropical forest plants as immunity. The results of the response analysis to this training concluded that (1) participants were very happy and interested in this activity, (2) this activity was useful, (3) participants understood how to make herbal tea and the syntax of PjBL Sudarmin, and (4) this learning was able to equip character conservation.